Prevention and management of soil erosion and torrential floods - Milutinović, Slobodan; Živkovic, Snezana, 1971- (Advances in environmental engineering and green technologies (AEEGT) book series., 2022)
"Chapter contributors to this publication discuss about the importance of the prevention and management practices of soil erosion and torrential floods, with respect to the exchange of knowledge and best practices with the aim to add value in sharing knowledge among different stakeholders to provide answers to the ongoing concerns in the changed climate conditions about the soil erosion and torrential floods prevention"--